Studi Literature: Analisis Keamanan dan Privasi Data Rekam Medis Elektronik Fasilitas Pelayanan Kesehatan Berdasarkan UU Nomor 27 Tahun 2022 - Adelia Inggrid Putri Maharani; Sinta Novratilova; Rina Wulandari; Dwi Rena Aulia; Azalia Tjandra Dewi; Aldi Juli Saputra (Lembaga Pengembangan Kinerja Dosen, 2026)
Data security in Electronic Medical Records (EMR) is a crucial issue in health information governance in Indonesia. This study evaluates the compliance of health facility information security systems with Ministry of Health Regulation (PERMENKES) No. 24 of 2022 and Personal Data Protection Law (UU PDP) No. 27 of 2022, and analyzes the impact of non-compliance on service quality and patient trust. The method employed is a systematic narrative literature review on the Google Scholar database (2023–2026) using the keywords